Persepsi Siswa Terhadap Penggunaan Metode Ceramah Dalam Pembelajaran SKI Materi Isra Mi’raj Di SDIT Annajah Bekasi - Basuki, Danang Dwi; Azizah, Nur; Aisyah, Aisyah; Haniifah, Alyaa Luthfi Nuur (Ibtida'iy : Jurnal Prodi PGMI, 2026)
This study aims to analyze students’ perceptions regarding the use of the lecture method during lessons using an Islamic Studies textbook on the Isra and Mi’raj at an elementary school in Bekasi. The study focuses on two main aspects: students’ level of understanding of the Isra and Mi’raj and their perceptions of the teacher’s use of the lecture method. The main issue is that one-way lecture methods are often considered ineffective in encouraging student participation, thus requiring evaluation from the students’ perspective to enhance learning motivation. Data collection was conducted through observation, interviews, and documentation, applying a qualitative descriptive methodology. Data analysis utilized categorization to classify students’ perceptions based on aspects of understanding and engagement with the Isra Mi’raj material. The findings indicate that the implementation of the lecture method shows that it can be used effectively if teachers vary their voice intonation, display communicative facial expressions, and deliver the material with an enthusiastic attitude. This approach prevents the learning process from becoming monotonous and helps students focus on learning activities. However, some students desire more interaction to avoid boredom.